Epidemiología de la discapacidad y desarrollo de la red de rehabilitación en la última década - Cuevas L., Gladys; Bunger B., Soledad (Revista Hospital Clínico Universidad de Chile, 2010)
Disability is a problem within the framework of human rights, that demands answers of the Chilean State in all areas of its work, and public health has had to develop strategies that enable it to assume the challenges of this growing group of our country presents.